2017
DOI: 10.1097/iop.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manuka Honey on Eyelid Wound Healing: A Randomized Controlled Trial

Abstract: Upper eyelid scars treated with or without Manuka honey heal well, without significant difference when assessed by validated scar grading scales; however, honey may provide subjective benefits early, postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…However, this study coincides with the findings of Boroumand et al [9], which showed that honey has analgesic effect after tonsillectomy. Malhotra et al [21] indicated to the early postsurgical benefits of honey application on eyelid wounds, which somewhat agrees with the results of the current study; VAS scores of Manuka side was significantly lower only in the first and second postoperative days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, this study coincides with the findings of Boroumand et al [9], which showed that honey has analgesic effect after tonsillectomy. Malhotra et al [21] indicated to the early postsurgical benefits of honey application on eyelid wounds, which somewhat agrees with the results of the current study; VAS scores of Manuka side was significantly lower only in the first and second postoperative days.…”
Section: Discussionsupporting
confidence: 93%
“…Experiments showed that it is free of any type of microorganisms [13]. It has been recently used safely in many clinical studies [1][2][3][4][5][6][7][8][9][10][11][12]21]. This study agreed, where no complication occurred regarding its use.…”
Section: Discussionsupporting
confidence: 56%
“…There has furthermore been demonstrated in vitro synergism between Manuka honey and conventional antibiotics, as measured by inhibition of bacterial growth or biofilm formation [2022]. As a topical agent, Manuka honey may be used effectively to treat disorders like atopic dermatitis, blepharitis, rhinosinusitis, and skin ulcers [2326]. Our data corroborate the measurable antimicrobial activity of Manuka honey against a spectrum of clinical isolates from skin and soft tissue sources, including those with multi-drug resistance such as MRSA, ESBL producers, CRE, and MDR P .…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 Cochrane review assessed the role of honey on various types of acute and chronic wounds and found some benefit for partial thickness burns and infected post-operative wounds, though the evidence was too heterogeneous and low quality to draw any firm overall conclusions [40]. Two recent prospective randomized controlled trials in the surgical literature assessed the effect of Manuka honey on surgical scar healing but found no significant difference compared to standard treatment modalities [41,42]. The role of honey in wound management is inconclusive and further investigation is warranted.…”
Section: Post-closure Wound Carementioning
confidence: 99%